Fe-doped GaN grown on stirring-assisted Na-flux process GaN thick film and its application on Ohmic contact UV detector. (January 2021) - Pan, Dali; Yang, Ruixia; Zhang, Song; Dong, Zengyin; Wang, Jian; Jin, Lei; Lan, Feifei; Wang, Zenghua
Abstract: Na-flux method is the most promising approach to grow GaN thick film substrate for GaN homoepitaxy. Here, the influence of solution stirring on grown GaN crystal morphology, crystal quality, dislocation density and impurity concentration was assessed for GaN crystal growth by Na-flux method. It is proved that the crystallinity, surface roughness and dominated orientation of the GaN thick layers are greatly influenced by stirring process, revealing a direct and correlated growth mechanism for the growth of GaN using Na-flux method. Notably, the surface roughness was reduced by three orders of magnitude under stirring (compared to un-stirred sample). This stirring-assisted GaN thick film was then used as seed layer to grow high resistance Fe-doped GaN epitaxial layer by applying HVPE method. On which Ohmic contact was successfully fabricated and an UV-detector with a high detectivity of ~10 13 Jones, which was among the highest values, and fast response (rise time of 100 ms, decay time of 160 ms) was obtained. Graphical abstract: Image 1 Highlights: Surface roughness of GaN thick film was improved for three orders of magnitude by using stirring assisted Na-flux method. Ohmic contact UV detector based on HVPE GaN grown on Na-flux GaN thick film with a high detectivity of ~10 13 Jones. Fast response and decay time of 100 ms and 160 ms was successfully obtained.